(untitled) (Polifonia, 1995)
ABSTRACT: This paper attempts to analyze a small set of oral invitations given and received between American-Brazilian, Brazilian-Brazilian and American-American interactions in the United States. Sociolinguistic differences on speech behavior may lead to painful cross-cultural confusuion and miscommunication. The distinction between American monochronic-time oriented invitations may lead Brazilians to think that Americans’ invitations are very difficult to negotiate because they are always "busy". Also, sometimes Americans courtesy may be understood as freindship by Brazilians.